a study on loss and gain in meaning of the conceptual metaphors denoting the concept of “death” in the english translations of trinh cong son’s songs - Võ,Phan Hải Quỳnh (ĐHĐN., 2014)
In light of Cognitive Linguistics, Metaphor not only is an important tool in human cognition and thought, but also plays a vital role in the conceptualization of “Death”. Abstract concepts like “Death” are commonly viewed and expressed in terms of conceptual metaphors. This study attempts to conduct a cross-linguistic research into the conceptual metaphors denoting “Death” in Trinh Cong Son’s songs. Under the framework of cognitive linguistics, the researcher looked into how metaphorical expressions were made use of in lyric songs and then pointed out all findings about the loss and gain in meaning used in “Death” metaphors through Trinh Cong Son’s songs and the English translational versions. These findings showed that translational versions of works of arts are more or less influenced by different languages and cultures. This study is also expected to be helpful for people whose works are in the fields of translation practice, cross-cultural communication and foreign language teaching and learning.